Validação do banco de itens Distúrbio do Sono e do banco de itens Distúrbio da Vigília do Patient-Reported Outcomes Measurement Information System (PROMIS®) para a população brasileira - Costa, Zilma Maria Severino Silva e (2019)
Introduction: Changes in sleep and wakefulness negatively affect the individual’s mood, memory and psychomotor performance, therefore quality of life instruments should be available for clinical evaluation of these factors. Objective: To validate the Patient-Reported Outcomes Measurement Information System (PROMIS®) Sleep Disturbance item bank and Wake Disturbance item bank for the Brazilian population. Material and Methods: The translated version to the Portuguese language of these two item banks was validated with 627 participants older than 18. The validation of these item banks was performed using Classic Test Theory (CTT), Item Response Theory (IRT), item calibration according to the graded response model (GRM) proposed by Samejima and analysis of Differential Item Functioning (DIF) according to the groups man and woman, healthy and carrier of chronic disease and Portuguese language and English language. Results: In relation to data quality, it was observed that there was no lost data, and five items of Sleep Disturbance item bank and four items of Wake Disturbance item bank had floor effect, and none item of the banks had ceiling effect. The internal consistency reliability with Cronbach’s alpha was α=0.96, and test-retest reliability with intraclass correlation coefficient was ICC=0.96 (CI0.95:0.95;0.96). In Exploratory Factor Analysis (EFA) the first extracted factor explained 37.55% of items total variance and, the second factor, 7.03%, whereas both factors explained 44.58% of items total variance. In Confirmatory Factor Analysis (CFA) to Sleep Disturbance bank the indices were RMSEA=0.099, SRMR=0.066, CFI=0.970 and NNFI=0.970; and for Wake Disturbance bank, RMSEA=0.110, SRMR=0.081, CFI=0.940 and NNFI=0.930. The calibration confirmed a good GRM adjustment and good sleep-wakefulness construct coverage with range of thresholds parameters in sleep construct from -3.22 to 4.46 and in wakefulness construct from -10.38 to 5.23. Regarding DIF, as the Sleep Disturbance bank as the Wake Disturbance bank showed homogeneous for the different groups tested. Although DIF is present in some items, it was insignificant, because the Nagelkerke pseudo R2 values were lower than 0.13. Conclusion: The version to the Portuguese language spoken in Brazil of PROMIS Sleep Disturbance and Wake Disturbance item banks demonstrated to be a reliable, accurate and valid measure with robust psychometric analysis and can be used in researches and clinical diagnoses.